Rekonstruksi Tanggung Jawab Keperdataan terhadap Pelanggaran Hak Cipta Lagu dalam Ekosistem Musik Digital di Indonesia - Farhan; Adnan; Ulfa widayati (Jurnal Hukum Lex Generalis, 2026)
The development of the digital music industry has given rise to increasingly complex forms of song copyright infringement through digital platforms and electronic monetization. This study aims to analyze civil liability for song copyright infringement and the effectiveness of copyright regulations in Indonesia. The method used is normative legal research with statutory, conceptual, case-based and comparative approaches. The results indicate that the protection of creators' economic rights, the distribution of digital royalties and the responsibilities of digital platforms still face implementation challenges. The Indonesian copyright legal system is also not fully capable of addressing the complexity of legal relationships in the modern digital music ecosystem.